Association of the bovine major histocompatibility complex (BoLA) BoLA-DRB3 gene with fat and protein production and somatic cell score in Brazilian Gyr dairy cattle (Bos indicus) - Nascimento,Carlos Souza do (2006)
The effect of the bovine major histocompatibility complex (BoLA) locus on animal health may be due to a direct action of its alleles on immune functions, whereas its indirect effect on production traits might be explained by the better general health conditions of more productive animals. In the present study, the BoLA-DRB3 gene was investigated in 1058 cows belonging to seven Brazilian Gyr Dairy herds (Bos indicus, Zebu cattle). A total of 37 alleles were identified, 15 of them described for the first time in a Zebu breed. A highly significant association (p < 0.02) was observed between allele *54 and a decrease (-26.1 kg) in milk protein yield and there was a significant association (p < 0.05) between this allele and lower (-26.07 kg) milk fat yield. There was also a significant association (p < 0.05) between allele *6 and decreased (-12.47 kg) milk protein and allele *7 and increased (12.72 kg) milk protein. There were also indications of association (p < 0.10) between somatic cell score (SCS) and alleles *3 (SCS increased by 0.54 units) and *31 (SCS increased by 0.46 units). The highly significant association of allele *54 with lower protein yield suggests the possible use of this allele in marker-assisted selection programs.